The toxicology of chrysotile-containing brake debris: implications for mesothelioma. (2nd January 2019) - Poland, Craig A.; Duffin, Rodger
Abstract: The global use of "asbestos" in various commercial products has led to a wide range and pervasive legacy of disease. One such use of chrysotile asbestos was brake pads and was utilized commonly in automobiles and heavy vehicles. The result of incorporation of chrysotile into brake pads is associated with the exposure of mechanics fitting and servicing vehicles to liberated chrysotile fibers. Despite the proven exposure, the relative risk of malignant mesothelioma (MM) in this occupational population is broadly seen as low. The toxicity of particulates, including fibers such as chrysotile, is driven by a combination of dose and physicochemical properties. As such, it is plausible that chrysotile released from brake pads may have undergone modification, thereby altering the pathogenicity profile. The impact of high sheer stress causing shortening of long fibers, heat modification, binding of resin matrix to the fiber surface on the relative toxicity of brake debris with regards to MM is considered. It is apparent that released chrysotile can undergo significant modification, reducing the long fiber dose although not all modifications may lead to reduced toxicity.